One-year unplanned readmission after percutaneous coronary intervention in ST-elevation myocardial infarction: rates, causes and predictors. (3rd October 2022) - Alkhalaila, O; Rahhal, A; Abdelghani, M S; Altermanini, M; Shehadeh, M; Shunnar, K; Barakat, M; Hailan, Y; Alkhateeb, M H; Habib, M B; Al-Hijji, M; Arabi, A R
Abstract: Introduction and aim: Unplanned readmission after percutaneous coronary intervention (PCI) in patients with ST-elevation myocardial infarction (STEMI) has a significant impact on the healthcare system. Nevertheless, most of the previous literature evaluated readmission within one month only post PCI without assessing the long-term readmission rates and predictors post-PCI. Therefore, we conducted a retrospective observational study to determine the rates, causes, and predictors of readmission post PCI among patients with STEMI over 1-year follow-up. Methods: We conducted a single-center retrospective observation cohort study. Study population included all patients who were admitted to the hospital with diagnosis of STEMI and underwent PCI during the same admission (index admission) and discharged alive in the period between Jan 1st, 2016 and Sep 30th, 2018. Patients were divided into two groups: those who had one or more unplanned readmission within one year after PCI and those who were not readmitted. Rates and causes of readmission within one year following PCI were reported. Predictors of readmission post-PCI were assessed using multivariate logistic regression and reported as odds ratio (OR) with p<0.05 indicating statistical significance. Results: A total of 1257 patients were included in our retrospective analysis. Most of the patients were male (95.9%). The mean age of the study population was 51±10. The most frequent culprit vessel was left anterior descending artery (LAD) in 56.3%. The median troponin T upon presentation was 47 ng/L [interquartile range: 171], with 25th percentile of 17 ng/L and 75th percentile of 2197 ng/L. Although around 70% of patients had reduced ejection fraction during the index admission, only 13.4% of the study population had clinical heart failure (HF). The unplanned readmission rate within one year post PCI was 11.5%, with 8.2% due to cardiac readmission while the remaining 3.3% due to non-cardiac causes. The most common cardiac causes for readmission were acute coronary syndrome and HF as shown in Table 1. As demonstrated in Table 2, positive predictors for all-cause readmission within one year after PCI among patients with STEMI were female gender (aOR= 4.14, 95% CI 2.10–8.18; p-value<0.001), chronic kidney disease (aOR= 2.76, 95% CI 1.07–7.08; p-value= 0.035), PCI using more than one stent (aOR= 1.66, 95% CI 1.09–2.55; p-value= 0.019) and clinical HF during index admission (aOR= 2.36, 95% CI 1.49–3.74; p-value<0.001). Conclusion: The rate of one-year unplanned readmissions after PCI among patients with STEMI was 11.5%, with acute coronary syndrome and HF as most common causes of cardiac readmission. We found that female gender, chronic kidney disease, PCI with more than one stent and clinical HF were associated with a significantly increased likelihood of readmission after PCI among patients with STEMI which may warrant close and frequent follow-up for these populations. Funding Acknowledgement: Type of funding sources: None.